2016
DOI: 10.3892/ol.2016.5419
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of S100A6 promotes cell proliferation in gastric cancer cells

Abstract: S100A6 is involved in regulating the progression of cancer. S100A6 can regulate the dynamics of cytoskeletal constituents, cell growth and differentiation by interacting with binding or target proteins. The present study investigated whether S100A6 affects cell proliferation in gastric cancer cells by stimulating several downstream factors. Firstly, the expression and localization of S100A6 were investigated using immunohistochemical staining, an immunoelectron microscopy and laser confocal scanning. A ChIP-Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“… 13 In gastric cancer, Wang et al found S100A6 had a remarkable increased expression in patients' tissues, and this overexpression had a clear correlation with high invasive cell behaviours, including positive lymph node involvement as well as vascular invasion. 14 Similar conclusions were also reached in pancreatic cancer and human nasopharyngeal carcinoma. 15 , 16 However, S100A6, along with another member‐S100A1, was considered to be associated with better prognosis in breast cancer patients.…”
Section: Discussionsupporting
confidence: 65%
“… 13 In gastric cancer, Wang et al found S100A6 had a remarkable increased expression in patients' tissues, and this overexpression had a clear correlation with high invasive cell behaviours, including positive lymph node involvement as well as vascular invasion. 14 Similar conclusions were also reached in pancreatic cancer and human nasopharyngeal carcinoma. 15 , 16 However, S100A6, along with another member‐S100A1, was considered to be associated with better prognosis in breast cancer patients.…”
Section: Discussionsupporting
confidence: 65%
“…Thus, it is important to detect the potential biomarkers or novel therapy of osteoarthritis. According to present studies, S100A6 was involved in cell survival and apoptosis in many cancer diseases, such as breast cancer 21 , malignant thyroid neoplasm 22 , gastric cancer 10 . However, owing to the deficiency of relevant researches about S100A6 roles in osteoarthritis, its biological functions and research value remain to be fully clarified.…”
Section: Discussionmentioning
confidence: 92%
“…The roles of S100A6 were widely discussed in the literature. Many studies have found the expression level of S100A6 associated closely with the physiological process of some cancer diseases and affect their apoptosis or proliferation activities, such as hepatocellular carcinoma, cervical cancer, and gastric cancer 8–10 . For other types of diseases, take myocardial infarction for example, researchers discovered the over‐expression of S100A6 inhibited the cell apoptosis and significantly improved the infarct size in vitro 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In total, 99 proteins (G/N>1.5) were identified to be upregulated and 66 proteins (G/N<0.667) were identified to be downregulated in the GMAH mesenchyma. The expression levels of the S100A6 and SOD3 proteins were different in the mesenchyma of the NGM and GMAH tissues, and were associated with tumorigenesis in previous studies ( 9 , 10 ). Fig.…”
Section: Resultsmentioning
confidence: 67%